2010
DOI: 10.1001/archgenpsychiatry.2009.185
|View full text |Cite
|
Sign up to set email alerts
|

Escitalopram and Enhancement of Cognitive Recovery Following Stroke

Abstract: Context Adjunctive restorative therapies administered during the first few months after stroke, the period with the greatest degree of spontaneous recovery, reduce the number of stroke patients with significant disability. Objective To examine the effect of escitalopram on cognitive outcome. We hypothesized that patients who received escitalopram would show improved performance in neuropsychological tests assessing memory and executive functions than patients who received placebo or underwent Problem Solving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
109
1
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 189 publications
(116 citation statements)
references
References 78 publications
2
109
1
4
Order By: Relevance
“…Recently, it was demonstrated that antidepressant use was beneficial to cognitive recovery when initiated during the first 3 months poststroke. 26 This was regardless of change in depression. Others have found that those with depression improvement demonstrated significantly better activities of daily living functional improvement then those without a remittance of depression.…”
Section: Resultsmentioning
confidence: 91%
“…Recently, it was demonstrated that antidepressant use was beneficial to cognitive recovery when initiated during the first 3 months poststroke. 26 This was regardless of change in depression. Others have found that those with depression improvement demonstrated significantly better activities of daily living functional improvement then those without a remittance of depression.…”
Section: Resultsmentioning
confidence: 91%
“…The efficacy of Selective Serotonin Reuptake Inhibitors (SSRI) in the treatment of anxiety and depressive disorders is well documented [45]. More recently escitalopram, the putative SSRI, has been shown to improve cognition and facilitate post-stroke recovery [46]. Taken together, there is growing evidence to substantiate the role played by serotonin in decision making process within the cognitive domain of executive function [47].…”
Section: Disc-1 Gene and Pde: Role In Schizophreniamentioning
confidence: 99%
“…In a study of 20 patients, citalopram also improved neurological status (NIH Stroke Scale) 45-50 days post-stroke, when compared with placebo [52]. The SSRI escitalopram was used in a study of 129 patients enrolled within 3 months after stroke and treated for 12 months [53]. Compared with patients treated with placebo or problem-solving therapy, those given escitalopram showed greater improvement in tests of cognitive function, including verbal and visual memory (Repeatable Battery for the Assessment of Neuropsychological Status), independent of depression.…”
Section: Antidepressants In the Treatment Of Strokementioning
confidence: 99%